2018
DOI: 10.3390/rs10010114
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Water Stress in Grapevines Using Proximal and Remote Sensing Methods

Abstract: Abstract:In light of climate change and its impacts on plant physiology, optimizing water usage and improving irrigation practices play a crucial role in crop management. In recent years, new optical remote sensing techniques have become widespread since they allow a non-invasive evaluation of plant water stress dynamics in a timely manner. Unmanned aerial vehicles (UAV) currently represent one of the most advanced platforms for remote sensing applications. In this study, remote and proximal sensing measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 55 publications
5
67
0
Order By: Relevance
“…In the context of precision agriculture, the application of UAS, their future prospects, and knowledge gaps are discussed in [53,[78][79][80][81]. While many horticultural crops have been studied using UAS technology, the most studied horticultural crops are vineyards [31,[82][83][84], citrus [85,86], peach [32,33], olive [18,87,88], pistachio [89,90], and almond [91][92][93][94], among others [95][96][97][98][99]. Some of the UAS types used for water status studies of horticultural crops are shown in Figure 2.…”
Section: Unmanned Aircraft Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of precision agriculture, the application of UAS, their future prospects, and knowledge gaps are discussed in [53,[78][79][80][81]. While many horticultural crops have been studied using UAS technology, the most studied horticultural crops are vineyards [31,[82][83][84], citrus [85,86], peach [32,33], olive [18,87,88], pistachio [89,90], and almond [91][92][93][94], among others [95][96][97][98][99]. Some of the UAS types used for water status studies of horticultural crops are shown in Figure 2.…”
Section: Unmanned Aircraft Systemsmentioning
confidence: 99%
“…Thus, such stress is reflected in the vegetation profile and easily captured by indices, such as NDVI. For this reason, NDVI has shown correlations with a wide array of crops response including vigour, chlorophyll content, leaf area index (LAI), crop water stress, and occasionally yield [34,[82][83][84]127]. The rededge band covers the portion of the electromagnetic spectrum between the red and NIR bands where reflectance increases drastically.…”
Section: Hyperspectralmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of the remote sensing approach is that large areas can be rapidly profiled obviating the need for a large number of measurements of individual vines that are time-and labour-intensive [18,25,26]. With the advent of high-resolution thermal cameras, sub-meter spatial resolution is now feasible from airborne platforms [27] allowing for the characterisation of water status of sub-blocks and even individual vines. Using an Unmanned Aerial Vehicle (UAV), Zarco-Tejada and co-workers evaluated a multispectral and thermal index and found a strong correlation with both g s and Ψ l in 'Thompson Seedless' grapevines in California [24].…”
Section: Introductionmentioning
confidence: 99%
“…Bellvert and colleagues mapped CWSI across an 11-ha Pinot Noir vineyard in Spain, finding a stronger correlation between CWSI and Ψ l at solar noon (1230 h) than in the morning (0930 h) [18]. Recently, Matese and co-workers determined CWSI and I g values under various irrigation regimes in two Italian vineyards planted with CAS and 'Cagnulari' [27]. All of the above-mentioned studies were undertaken using UAV platforms, which are limited by range (flight time) and therefore not suited to characterising entire viticultural regions or even large vineyard blocks.…”
Section: Introductionmentioning
confidence: 99%